ANALYSIS OF THE INFLUENCE OF LEARNING MEDIA ON MI STUDENTS' INTEREST IN LEARNING IN TANJUNG PURA - Husnah, Diah Hafizhotul (Universitas Labuhanbatu, 2024)
This research aims to describe the influence of the use of learning media on students' interest in learning and learning outcomes at MI Tanjung Pura. The background to this research is the use of learning media which is rarely used in learning. Lack of student interest is influenced by the learning process which is considered boring or lacking in variety. As well as a lack of motivation to learn in the learning process which results in a lack of student understanding of the learning material so that learning outcomes decrease. This research is field research using a quantitative approach with survey research methods. The research population was 174 students and the sample in this study was 63 students from grades 1 to 6 at Kaliputih State Elementary School. The data collection methods used are questionnaires and documentation. The data analysis technique used is simple linear regression analysis. The results of this research show that there is a significant influence of the media and students' interest in learning on the learning outcomes of students in grades 1 to 6 at MI Tanjung Pura. The magnitude of the influence of media and interest in learning on student learning outcomes is 0.699, which means that media and interest in learning influence learning outcomes by 69.9%, while the remainder is influenced by other factors not discussed in the research.Keywords: Learning Media, Interest in learningAbstrak Penelitian ini bertujuan untuk mendeskripsikan pengaruh penggunaan media pembelajaran terhadap minat belajar dan hasil belajar siswa di MI Tanjung Pura. Adapun latar belakang penelitian ini adalah penggunaan media pembelajaran yang jarang digunakan dalam pembelajaran. Kurangnya minat siswa yang dipengaruhi oleh proses pembelajaran yang dianggap membosankan atau kurang bervariasi. Serta kurangnya motivasi belajar dalam proses pembelajaran yang mengakibatkan kurangnya pemahaman siswa terhadap materi pembelajaran sehingga hasil belajar mengalami penurunan. Penelitian ini merupakan penelitian lapangan dengan menggunakan pendekatan kuantitatif dengan metode penelitian survey. Populasi penelitian adalah 174 siswa dan sampel dalam penelitian ini adalah 63 siswa dari kelas 1 s/d 6 di SD Negeri Kaliputih. Metode pengumpulan data yang digunakan adalah angket dan dokumentasi. Teknik analisis data yang digunakan yaitu analisis regresi linier sederhana. Hasil penelitian ini menunjukkan bahwa ada pengaruh yang signifikan dari media dan minat belajar siswa terhadap hasil belajar siswa kelas 1 s/d 6 di MI Tanjung Pura. Adapun besarnya pengaruh media dan minat belajar terhadap hasil belajar siswa adalah sebesar 0,699 yang berarti bahwa media dan minat belajar berpengaruh terhadap hasil belajar sebesar 69,9%, sedangkan sisanya dipengaruhi oleh faktor lain yang tidak dibahas dalam penelitian.Kata Kunci: Media Pembelajaran, Minat belajar